(untitled) (International Journal of Mathematics and Physics, 2013)
In this paper the mathematical model of vertical-axis Darrieus wind turbine (carousel type etc.). The paper presents a mathematical formulation of the problem, method of calculating the angular velocity of the Darrieus wind power generating apparatus when exposed to the incoming flow and the results obtained from the calculation. According to the calculations, below the established methodology, the reliable results that well represents the physics of the phenomenon. The mathematical model and its numerical implementation and the results may be useful to further improve the mathematical description of the problem in the design and construction of vertical-axis wind turbines.